STRONGLY AND PERFECTLY 〖Iα〗_G^⋀-CONTINUOUS FUNCTION IN INTUITIONISTIC TOPOLOGICAL SPACES (Journal of Namibian Studies : History Politics Culture, 2023)
The concept of intuitionistic sets and intuitionistic points in topological spaces was first introduced by Coker. The purpose of this paper is to introduce a mapping of strongly -continuous and perfectly -continuous function in intuitionistic topological spaces and analyze its relations with other existing intuitionistic functions.